Modifikasi Sudut Masuk Impeller Pompa Sentrifugal Untuk Mengurangi Efek Kavitasi - Arini, Nu Rhahida; Ramadhani, Desy; Diana, Lohdy; Reivanda, Reihan Rizky (Journal of Applied Civil Engineering and Infrastructure Technology, 2025)
A centrifugal pump utilizes pressure energy, which is generated by the kinetic energy of involute impeller rotation. A common issue in pump operation is cavitation, a physical phenomenon that occurs when the static pressure of the fluid drops below its saturation pressure, causing the fluid to boil. This phenomenon affects the pump, leading to problems such as shockwaves and erosion, which must be minimized. This research aimed to investigate the influence of pump impeller modifications in reducing the cavitation effect using the computational fluid dynamics (CFD) method. The modifications focused on adjusting the inlet and outlet angles of the pump impeller. A 3D CFD model was developed using OpenFOAM, a CFD software tool, and the cavitation number (Ca) was used as the primary parameter to measure cavitation levels. Additionally, Ca was compared to a reference cavitation number, calculated based on the saturated pressure, while cavitation points at the impeller inlet and outlet were visualized using Paraview software. The results showed that a pump impeller with a blade inlet angle (β₁) of 21,69° resulted in 39.157 cavitation points, whereas modifying β₁ to 38,66° reduced the cavitation points to 32.778, thus decreasing the cavitation points by 6.379. This confirmed that modifying β₁ significantly reduces the cavitation effect.